Miarkowanie kary umownej - Śmieja, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
After briefly presenting the essence of contractual penalties according to Polish civil law, the author goes on to discuss two situations where — according to art. 484 § 2 of the Civil Code— the court, at the request of the debtor, may reduce the amount of the contractual penalty, namelyin the following cases: 1. when the obligation has been performed to a significant degree, and 2. when the contractual penalty is grossly excessive. By presenting various views on science and jurisprudence, the author analyzes the prevailing interpretative concepts in this area, and then attempts to respond to them.
Keywords: contractual penalty; contractual penalty moderation; grossly excessive contractual penalty